Comparative Genomic Analysis of Delftia tsuruhatensis MTQ3 and the Identification of Functional NRPS Genes for Siderophore Production - Guo, Haimeng (Biomed Res Int, 2016)
Plant growth-promoting rhizobacteria (PGPR) are a group of rhizosphere bacteria that promote plant growth. Delftia tsuruhatensis MTQ3 is a member of PGPR that produces siderophores. The draft genome sequence of MTQ3 has been reported. Here, we analyzed the genome sequence of MTQ3 and performed a comparative genome analysis of four sequenced Delftia strains, revealing genetic relationships among these strains. In addition, genes responsible for bacteriocin and nonribosomal peptide synthesis were detected in the genomes of each strain. To reveal the functions of NRPS genes in siderophore production in D. tsuruhatensis MTQ3, three NRPS genes were knocked out to obtain the three mutants MTQ3-Δ1941, MTQ3-Δ1945, and MTQ3-Δ1946, which were compared with the wild-type strain. In qualitative and quantitative analyses using CAS assay, the mutants failed to produce siderophores. Accordingly, the NRPS genes in MTQ3 were functionally related to siderophore production. These results clarify one mechanism by which plant growth is promoted in MTQ3 and have important applications in agricultural production.